2010
DOI: 10.2807/ese.15.17.19552-en
|View full text |Cite
|
Sign up to set email alerts
|

Mass immunisation campaign in a Roma settled community created an opportunity to estimate its size and measles vaccination uptake, Poland, 2009

Abstract: During a mass immunisation campaign following an outbreak of measles in a Roma community settled in the town of Pulawy, Poland, we performed an estimation of the size of this Roma population and an assessment of its vaccination uptake. We obtained a list of Roma residing in Pulawy from the local municipality and estimated using a simple capture-recapture formula that Pulawy had 377 Roma residents (43% under 20 years old), which was 27% more than the 295 registered at the municipality. During the vaccination ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…Data provided by the EpiSouth survey not only confirmed previous studies [2,[27][28][29] that identified low immunization coverage and/or presence of outbreaks as a major issue among particularly vulnerable mobile communities [30]. It also provided evidence that this is not only an EU problem [24,31] but affects countries across the Mediterranean region.…”
Section: Formal Barriers and Legislationsupporting
confidence: 80%
“…Data provided by the EpiSouth survey not only confirmed previous studies [2,[27][28][29] that identified low immunization coverage and/or presence of outbreaks as a major issue among particularly vulnerable mobile communities [30]. It also provided evidence that this is not only an EU problem [24,31] but affects countries across the Mediterranean region.…”
Section: Formal Barriers and Legislationsupporting
confidence: 80%
“…This enabled us to identify differences and similarities in views within each community as well as draw out meaningful comparisons across the six Traveller communities, both for gender and for different vaccines (childhood and adult). A small number of studies have reported the uptake of immunisation by different groups of Travellers in the UK 1,44,45,47 and Roma communities in Europe; [108][109][110] and an extensive literature exists on Travellers' experiences of health services more generally. [17][18][19][20][21][22]24 However, there is very little research on Travellers' views on, and experiences of, immunisation specifically.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Yet there is little research on the factors associated with immunisation among Roma, in part because of a lack of appropriate data in this hard to reach population 1 . What research does exist focuses on one or a few districts in a single country, often with a very small number of observations 14 15 and authors have repeatedly noted the importance of achieving a better understanding of this issue [16][17][18] . We investigate differences in child vaccination coverage between Roma and non-Roma living in proximity to them, seeking to understand determinants of the vaccination gap, including access to health care and discrimination faced by Roma.…”
Section: Introductionmentioning
confidence: 99%